Alternative to the right-hand rule: Farah’s method - Farah, Mo’ath (European Scientific Journal, ESJ, 2025)
Right-hand rule (RHR), the conventional tool to establish directions of magnetic field and force in electromagnetism, is hard to use because it involves hand motions and three-dimensional visualisation. This paper presents an alternative approach, called Farah’s Method, using rotation of Cartesian coordinate axes rather than hand movements, so students can learn it more easily and with less mental burden, as the proposed method is based on the rotation between the axes.. A challenge encountered in this study was the lack of available resources addressing an alternative approach to the right/left-hand rules. In a quasi-experimental study involving 60 secondary school students, we compared Farah’s Method to the RHR through pre- and post-tests with conceptual and problem-solving activities, as shown in Figures 11-13. Under the Farah’s Method condition, there were significantly improved post-test scores (80.47% vs. 61.27%, p < 0.001), better problem-solving accuracy (87.63% vs. 66.87%), shorter response latencies (35.87 s vs. 53.12 s), and lower self-reported cognitive load (overall rating: 4.31 vs. 3.70). These results draw attention to the method’s capacity to simplify vector analysis into concise, significant aspects and foster conceptual understanding. This method is also compatible with learning technologies such as PhET simulations and virtual reality interfaces, where coordinate rotations can be dynamically visualised, making it easier to implement in digital learning environments. This approach has future uses in STEM fields such as mechanics and engineering and offers an accessible, scalable pedagogy for overcoming spatial reasoning obstacles. The research implies that Farah’s Method is preferable to the RHR with excellent prospects for revolutionising electromagnetism teaching via technology-enhanced learning.